2022
DOI: 10.4085/1062-6050-0605.21
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Instability, Pain, and Psychological Factors for Prediction of Function and Disability in Individuals With Chronic Ankle Instability

Abstract: Context: Chronic ankle instability (CAI) is associated with residual instability, pain, decreased function, and increased disablement. Injury-related fear has been associated with CAI, although its relationship to other impairments is unclear. The Fear-Avoidance Model is a theoretical framework hypothesizing a relationship between injury-related fear, chronic pain, pain catastrophizing, and disability. It has been useful in understanding fear's influence in other musculoskeletal conditions bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The 74 articles identified by the systematic review included a total of 13388 participants aged 11 to 85 years, including 7308 women, 4729 men, and 1351 participants whose gender and sex was not reported. The studies investigated populations with pain (n = 37) 62,6471,73,7681,83,88,89,111128 cardiac conditions (n = 6) 86,87,104,129131 , surgery (n = 8) 63,131137 , arthritis (n = 10) 75,82,84,85,91,138142 , neurologic conditions (n = 3) 90,143,144 , pulmonary conditions (n = 3) 145147 , cancer (n = 1) 74 , women health conditions (n = 2) 72,148 , as well as healthy adults (n = 6) 29,85,107,149151 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 74 articles identified by the systematic review included a total of 13388 participants aged 11 to 85 years, including 7308 women, 4729 men, and 1351 participants whose gender and sex was not reported. The studies investigated populations with pain (n = 37) 62,6471,73,7681,83,88,89,111128 cardiac conditions (n = 6) 86,87,104,129131 , surgery (n = 8) 63,131137 , arthritis (n = 10) 75,82,84,85,91,138142 , neurologic conditions (n = 3) 90,143,144 , pulmonary conditions (n = 3) 145147 , cancer (n = 1) 74 , women health conditions (n = 2) 72,148 , as well as healthy adults (n = 6) 29,85,107,149151 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Most of these questionnaire-based studies used the short form of the International Physical Activity Questionnaire (IPAQ-SF; n = 20) 29,73,76,78,79,82,85,86,112,114,116,130,131,133,138141,146,147 which consists of 6 items assessing time spent in light (i.e., walking), moderate (e.g., carrying light loads, cycling at moderate speed, doubles tennis), and vigorous physical activity (e.g., digging, fast cycling, heavy lifting, aerobics) over the last 7 days 159 . Other questionnaires were used to assess physical activity, such as the Baecke Habitual Physical Activity Questionnaire 160 (BHPAQ; n = 5) 64,89,90,107,113 , Saltin-Grimby Physical Activity Level Scale 161 (SGPALS; n = 5) 80,104,115,125,135 , Godin-Shephard Leisure-Time Exercise Questionnaire 162 (GLTEQ; n = 2) 121,134 , Minnesota Leisure Time Physical Activity Questionnaire 163 (MLTPAQ; n = 1) 136 , Physical Activity Scale for the Elderly 164 (PASE; n = 2) 123,149 , Physical Activity Questionnaire for the Elderly 164 (PAQE; n = 1) 72 , Short Questionnaire to Assess Health Enhancing Physical Activity 165 (SQUASH; n = 1) 142 , the Tegner Assessment Scale 166 (TAS; n = 1) 63 , University of California Los Angeles (UCLA) activity score 167 (n = 1) 84 , Leisure Time Physical Activity Index 168 (LTPAI; n = 1) 67 , Global Physical Activity Questionnaire 169 (GPAQ; n = 2) 77,83 , Freiburger Questionnaire on Physical Activity 170 (FQPA; n = 1) 127 , Jurka Physical Activity Scale 171 (JPAS; n = 1) 81 , Rapid Assessment of Physical Activity questionnaire 172 (RAPAQ; n = 1) 68 , Tecumseh Occupational Activity Questionnaire 173 (TOAQ; n = 1) 136 , and Australian Health Survey-derived questions (AHS; n = 1) 71 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with CAI were found to have injury-related fear that prevented them from rehabilitation training and returning to sports, leading to disuse of function, which further limited the recovery of the functional activity of ankles [51]. Suttmiller et al [23] recruited 126 CAI patients and evaluated the results of multiple pain and ankle function questionnaires. It was concluded that pain was strongly associated with worse ankle function, and pain might be a predictive factor of decline in the function of ankle joints.…”
Section: Discussionmentioning
confidence: 99%
“…The NRS-11 is a segmented numeric version of the Visual Analog Scale (VAS) in which a respondent selects a whole number (0-10 integers) that best reflects the intensity of their pain [20]. Previous literature related to CAI that measured pain intensity on a numeric rating scale used a score > 0 to define the presence of pain [21][22][23]. Therefore, the presence of pain was determined if subjects rated their pain as no less than 1.…”
Section: Participantsmentioning
confidence: 99%